Supplier Assessment For Composites’ Product-Based Manufacturers: Case Study - Wan Mahmood, Wan Hasrulnizzam; Saedin, Mohd Rizal; Muhamad, Mohd Razali (Publications International Lahore, Pakistan, 2014)
Supplier assessment as a method to company for choosing the potential supplier; it is important decision makings in business operation. This paper examines the similarities and differences of supplier assessment methodology on four selected companies which involved in composites products and manufacturing. The data collections consist of semi-structured interview with supply chain personnel, documentation review and observation. The findings show that effective supplier assessment is not easy to achieve and it takes knowledge or an organization’s goals, supply base, business processes, and structure. Besides, the study identified that different companies (same business nature but different product) have their own ways in selecting out the main criteria in supplier assessment that in line with their business strategy. The results can be used as reference to the others companies to restructure their supplier assessment focusing on the main criteria based on their business objective.